1998
DOI: 10.1111/j.1442-9071.1998.tb01318.x
|View full text |Cite
|
Sign up to set email alerts
|

The Heimann‐Bielscholwsky phenomenon: Dissociated vertical nystagmus

Abstract: We believe that the HBP may be a reasonably common condition, although very under diagnosed. This condition may be similar to Central Fusion Disruption. Patients with HBP appear to have lost the potential for fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…4,5 Second, the Heimann-Bielschowsky movements have been described as nystagmoid with pendular vertical oscillations about the horizontal meridian. [9][10][11] In contrast, the eye movements in our cases were not truly rhythmic or nystagmoid, but were more sporadic and therefore similar to that of the more common hypertropic DVD. 7,8,12 Case 2 is the first case, to our knowledge, that presents eye movement recordings of the hypotropic drifts in a case of dissociated hypotropia.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…4,5 Second, the Heimann-Bielschowsky movements have been described as nystagmoid with pendular vertical oscillations about the horizontal meridian. [9][10][11] In contrast, the eye movements in our cases were not truly rhythmic or nystagmoid, but were more sporadic and therefore similar to that of the more common hypertropic DVD. 7,8,12 Case 2 is the first case, to our knowledge, that presents eye movement recordings of the hypotropic drifts in a case of dissociated hypotropia.…”
Section: Discussioncontrasting
confidence: 65%
“…The visual acuity levels in these eyes were usually worse than 6/60, but the condition has been described in eyes with visual acuities better than 6/60. 11 The onsets of the vision deficits have ranged from infancy to 50 years of age. 9,10 In common with our cases, the velocity of the movements are reported to be slow, up to 5 cycles per second, and the amplitudes are variable, ranging from 5 to 50 degrees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, both Heimann and Bielschowsky pointed at the role of absent fusion (either nonacquired or disrupted) in HBP. Davey et al have suggested that HBP could be due to central fusion disruption (CFD) [12]. If CFD may well explain the loss of stability of the disabled eye in HBP, it does not explain the characteristic oscillations of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al reported cases of improvement of oscillations following strabismus surgery, whereas Davey et al did not observe any reduction in oscillation after strabismus surgery. 4,5 Our patient underwent rectus muscle resection, which could have had a similar effect to tenotomy. Therefore, this case suggests that surgery performed on horizontal extraocular muscles could be an effective treatment for HeimannBielschowsky phenomenon.…”
Section: Commentmentioning
confidence: 99%